Seminars winter term 2004/2005 / Mathematisches Institut, Georg-August-Universität Göttingen. Yuri Tschinkel (ed.) - Tschinkel, Yuri (Universitätsdrucke Göttingen$aSeminare / Mathematisches Institut, 2005)
This volume contains lecture notes from the seminars αNumber Theory±, αAlgebraic Geometry± and αTwisted Cohomology Theories± which took place at the Mathematics Institute of the University of Göttingen during the Winter Term 2004/2005. Most contributions report on recent work by the authors.